1992
DOI: 10.1021/om00037a085
|View full text |Cite
|
Sign up to set email alerts
|

Pressure acceleration of [2 + 2] cycloaddition reactions on the coordinated ligand of chromium and tungsten pentacarbonyl carbene complexes

Abstract: The influence of pressure on [2 +-21 cycloaddition reactions of a,P-unsaturated Fischer carbene complexes (M = Cr, W) with 3,4-dihydro-2H-pyran was studied. The cycloaddltion was found to be sensitive toward pressure and showed a remarkable rate acceleration independent of the metal center. The temperature, pressure, and solvent dependence of these reactions was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 2 publications
0
9
0
2
Order By: Relevance
“…[25] It was concluded REVIEWS Fischer Carbene Complexes in Organic Synthesis from kinetic measurements on the temperature and pressure dependence that the model reaction of dihydropyran (46) with 39 involves a synchronous, single-step process with a nonpolar transition state. [28] A spontaneous cycloreversion [30] to butadien-2-ylcarbene complexes is sometimes observed after a successful [22] cycloaddition, [25,26,29,31] as for example in the reaction of 48 (M Cr) with ethyl 3,3-diethoxyacrylate (49), which leads to the complex 50. [29] The total product spectrum from 48 (M Cr) and 49 appears somewhat bizarre, for in addition to 50 two pyranylidene complexes 51 (R H, Et) analogous to product 45 (see above), and the binuclear biscarbene complex 52 are found.…”
Section: With Dienes and Electron-rich Alkenesmentioning
confidence: 99%
“…[25] It was concluded REVIEWS Fischer Carbene Complexes in Organic Synthesis from kinetic measurements on the temperature and pressure dependence that the model reaction of dihydropyran (46) with 39 involves a synchronous, single-step process with a nonpolar transition state. [28] A spontaneous cycloreversion [30] to butadien-2-ylcarbene complexes is sometimes observed after a successful [22] cycloaddition, [25,26,29,31] as for example in the reaction of 48 (M Cr) with ethyl 3,3-diethoxyacrylate (49), which leads to the complex 50. [29] The total product spectrum from 48 (M Cr) and 49 appears somewhat bizarre, for in addition to 50 two pyranylidene complexes 51 (R H, Et) analogous to product 45 (see above), and the binuclear biscarbene complex 52 are found.…”
Section: With Dienes and Electron-rich Alkenesmentioning
confidence: 99%
“…Later, the authors have shown 210 that the major part of complex 109 is not formed via the slow cyclization of 108 to 109, but through an independent pathway. The results of a study 211 on the temperature, pressure, and solvent dependence of the [2+2] cycloaddition of 100 (M ) Cr, R ) Me) to 3,4-dihydro-2H-pyran indicate a nonpolar concerted, synchronous one-step mechanism. The nature of R in 100 (M ) Cr) has been shown to be crucial to the course of the reaction with methyl isopropenyl ether.…”
Section: B [2+2] Metal-assisted Cycloaddition Reactionsmentioning
confidence: 99%
“…It implies that the reaction may involve an enhanced resonance transition state. The magnitude of ρ + obtained from the Hammett plot (−1.19) is quite different from those observed for typical ionic processes (−3.3 to −4.3) and is comparable with other concerted [3 + 2] cycloaddition 2 Plot of log( k X / k H ) verse σ p + for reaction of 2 with substituted PBN. 3 Substitutent Effect on Nitrone (reaction of 2 with 4a − g ) nitroneXσ p o a σ p + a k (10 -3 M -1 s -1 ) 4a Me 2 N −0.32 −1.7 13700 4b MeO −0.12 −0.78 1010 4c Me −0.14 −0.3 440 4d H 0 0 230 4e Br 0.26 0.15 67 4f Cl 0.34 0.11 68 4g NO 2 0.81 6 a From ref .
…”
Section: Resultsmentioning
confidence: 68%